Students' learning styles and their academic performance in biology - De La Cruz, Mark Eroll S (University of the Philippines Visayas, 2019)
This quantitative descriptive research was conducted to determine the students' learning styles and their academic performance in Biology. Kolb's learning Style Inventory version 3.1 was used to determine the respondents' learning stylesThe learning styles were classified as accommodating, diverging, assimilating or converging. The academic performance in Biology of the respondents were determined based on their scores using a validated researcher-made achievement test. The study was conducted last February, 2018 on 118 Grade 10 students of Salvacion National High School in Nueva Valencia, Guimaras. The majority of the respondents (47%) had diverging as their learning style. The mean achievement score was 13.60+4.34 SD and is interpreted as approaching proficiency. Mann-Whitney test was used to determine the significant difference in respondents' academic performance i Biology when grouped according to sex and age, and learning styles when grouped according to sex and age. The Kruskal-allis test was used to determine the significant difference in respondents' academic performance in Biology when grouped by monthly family income, and academic performance in biology when grouped by learning styles.Data revealed that learning style had significant difference with monthly family income (p=.046) but not with sex (p=.056) and age (p=.736). Further, there were significant differences between the respondents' academic performance in Biology when grouped according to sex (p=.021), age (p=.007) and monthly family income (p=.000). There was a significant difference (p=.004) in respondents' academic performance in biology when grouped according to learning styles. All p-value were set at .05 significance level. It was also founf out that students with accomodating and converging learnng styles performed higherr in achievement test in Biology than students with diverging and assimilating learning styles. The researcher suggested that more consideration should be given to teaching styles to match and to accommodate students' learning styles in order to improve the academic performance of students i Biology.